1998
DOI: 10.1093/carcin/19.2.347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking cessation on oxidative DNA modification estimated by 8-oxo-7,8-dihydro-2'-deoxyguanosine excretion

Abstract: Smoking cessation significantly reduces the urinary excretion rate of 8-oxodG, giving direct and controlled evidence that cigarette smoking causes an increased rate of oxidative DNA modification. This could represent a mechanism by which tobacco smoke is carcinogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…Interestingly, treatment with oxidants has been shown to cause similar mutations in codons 248 -250 of p53 (Hussain et al, 1994). Prieme et al (1998) found a statistically significant effect of smoking cessation for 4 and 26 weeks on the urinary excretion rate of the DNA repair products between the control group and the smoking cessation group. The study gives direct evidence that smoking induces oxidative DNA modification.…”
Section: Cigarette Smokementioning
confidence: 79%
“…Interestingly, treatment with oxidants has been shown to cause similar mutations in codons 248 -250 of p53 (Hussain et al, 1994). Prieme et al (1998) found a statistically significant effect of smoking cessation for 4 and 26 weeks on the urinary excretion rate of the DNA repair products between the control group and the smoking cessation group. The study gives direct evidence that smoking induces oxidative DNA modification.…”
Section: Cigarette Smokementioning
confidence: 79%
“…Leanness may represent decreased biological functions against oxidative DNA stress induced by smoking and thus could be used as a marker of host susceptibility to smoking-related cancer. Because smoking cessation leads to a substantial decline of 8-OHdG levels (20), it is expected that lean smokers may have large health benefit from smoking cessation. It remains uncertain, however, whether leanness itself or factor related to leanness modulates the carcinogenic effect of smoking, and this point deserves further investigations, including a search for genetic profiles regarding metabolism of tobacco smoke or repair of DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the potentially confounding effects of a set of baseline values of established risk factors for breast cancer: parity (yes/no), number of births (linear), age at first birth (linear), length of school education (short, medium, long), duration of HRT (linear), BMI (linear), and alcohol intake (linear) as well as smoking status (never, former, current), duration (years), and intensity (g/day), which has a known effect on 8-oxodG excretion (35). The choice of potential confounders was based on the information obtainable from the questionnaire and a literature-based assessment of the most important variables.…”
Section: Methodsmentioning
confidence: 99%